2002
DOI: 10.1128/jb.184.16.4442-4448.2002
|View full text |Cite
|
Sign up to set email alerts
|

Purification, Overproduction, and Partial Characterization of β-RFAP Synthase, a Key Enzyme in the Methanopterin Biosynthesis Pathway†

Abstract: Methanopterin is a folate analog involved in the C 1 metabolism of methanogenic archaea, sulfate-reducing archaea, and methylotrophic bacteria. Although a pathway for methanopterin biosynthesis has been described in methanogens, little is known about the enzymes and genes involved in the biosynthetic pathway. The enzyme ␤-ribofuranosylaminobenzene 5-phosphate synthase (␤-RFAP synthase) catalyzes the first unique step to be identified in the pathway of methanopterin biosynthesis, namely, the condensation of p-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(89 citation statements)
references
References 42 publications
4
85
0
Order By: Relevance
“…1). The specific activity for the enzyme in the cell extract of induced cells was 10.0 nmol of ␤-RFA-P produced per min/mg of protein, in agreement with the enzyme from Archaeoglobus fulgidus (4). Overexpression of the protein was probed by using anti-His tag antibodies and antibodies raised against the pure protein, which stained a band around 37 kDa, indicating that this is the protein of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). The specific activity for the enzyme in the cell extract of induced cells was 10.0 nmol of ␤-RFA-P produced per min/mg of protein, in agreement with the enzyme from Archaeoglobus fulgidus (4). Overexpression of the protein was probed by using anti-His tag antibodies and antibodies raised against the pure protein, which stained a band around 37 kDa, indicating that this is the protein of interest.…”
Section: Resultsmentioning
confidence: 99%
“…Even though H 4 MPT is found in Archaea and one class of Bacterium (e.g. Methylobacterium extorquens), the biosynthetic pathway for these two folates (folate and methanopterin) is different suggesting that they play different functional roles in physiology of the cell (4,5). We are targeting this enzyme to inhibit specifically methanogenesis (6), which has the potential impact of reducing the levels of the greenhouse gas methane, which has doubled over the last 200 years.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In all four Planctomycete genomes, ORF19 was found to be linked to mptG. ORF19 is involved in H 4 MPT biosynthesis , while mptG codes for b-RFAP synthase, an enzyme that catalyzes the first reaction distinguishing the methanopterin biosynthesis pathway from that of folate biosynthesis (Scott and Rasche, 2002;Chistoserdova et al, 2004 Genes involved in the H 4 MPT-linked C1 metabolism were also found on two of the four fosmids from the Namibian OMZ (Table 3 and Figure 2). Fosmid 6FN harbors an instance of fmdC plus the gene mobA that encodes the molybdopterin-guanine dinucleotide biosynthesis protein A. Fosmid 8FN contains a larger C1 module comprising ORF20-pabB-pabA-ORF19-mptG.…”
Section: Ecology Of Planctomycete D Woebken Et Almentioning
confidence: 99%